Analysis of an astounding aggregation of Ranzania laevis (Molidae: Actinopterygii) in the tropical south‐western Atlantic. Issue 4 (10th August 2016) - Horn, T. S.; Machado, R.; Weiss, C. V. C.; Giora, J.; Malabarba, L. R.
Abstract : Unusual catches of more than 4200 kg of the slender sunfish Ranzania laevis are described from the south‐western Atlantic, corresponding to the largest aggregation records for the species. These unexpected records were associated with unusually warm currents in the area. Males and females were physiologically able to spawn at the moment of capture, suggesting the occurrence of reproductive aggregation in this species.